Associations between the occurrence of the ACTN3 R577X, ACE I/D, BDKRB2 +9/-9 polymorphisms and anaerobic performance among a group of elite fencers - Balko, I.; Balko, S.; Petr, M.; Heidler, J.; Benesova, L.; Kohlikova, E. (Physical Activity Review, 2021)
Itroduction: This research aims to detect possible associations between the ACTN3 R577X, ACE I/D, BDKRB2 +9/-9 genetic polymorphisms, and selected anaerobic performance indicators among elite and sub-elite fencers. Methods: The sample of participants included a group of 20 fencers (males, age 25.5 ± 6.9 years; height 185.1 ± 5.8; weight 78.3 ± 9.8). We obtained genotype analysis for selected polymorphisms ( ACTN3 R577X, ACE I/D, BDKRB2 +9/-9) through buccal swabs. 30-second Wingate test was used for the anaerobic performance where the following variables were monitored: the maximal anaerobic performance - Pmax [W], the anaerobic capacity - AnC [kJ], the total number of revolutions - TR [n], the peak blood lactate concentration - LA peak [mmol·l-1]. Results: Within ACTN3 R577X polymorphism, no differences were found in the observed variables between genotypes. However, ACE I/D heterozygotes reached higher P max, AnC, and LA peak values than homozygotes. Furthermore, BDKRB2 +9/-9 polymorphism homozygotes with -9 allele reached higher P max and AnC values than homozygotes with +9 allele. No statistical differences were found in all monitored variables between genotypes of monitored polymorphisms. Conclusions: The research findings might serve as another useful piece of knowledge related to the existing statements in the field of genetics, focusing on speed-strength performance problems. It should be highlighted that current studies are only the first steps in helping us better understand the associations between genetic factors and performance in sports